2017
DOI: 10.1111/ceo.12953
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bleb morphology between trabeculectomy and deep sclerectomy using a clinical grading scale and anterior segment optical coherence tomography

Abstract: Importance: The role of the filtration bleb for IOP management following trabeculectomy (TRAB) and deep sclerectomy (DS) in glaucoma is highlighted in this study.Background: This study serves to analyse the bleb morphology and IOP using the Indiana Bleb Appearance Grading Scale (IBAGS) and the anterior-segment optical coherence tomography (AS-OCT) postoperatively and at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…IBAGS and AS-OCT have been used by Oh et al [ 38 ] to present a comparison of bleb morphology between trabeculectomy and deep sclerectomy. Three months postoperatively, on the clinical grading, their trabeculectomy group had significantly higher, broader, and less vascular blebs than the eyes after deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
“…IBAGS and AS-OCT have been used by Oh et al [ 38 ] to present a comparison of bleb morphology between trabeculectomy and deep sclerectomy. Three months postoperatively, on the clinical grading, their trabeculectomy group had significantly higher, broader, and less vascular blebs than the eyes after deep sclerectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitation of WBCS is that it is not always possible to grade microcysts in every part of the filtering bleb solely from photographs, and therefore, some cases might need the help of a slit lamp [28]. Through this pilot observation, we found that the iPhone X images were comparable to slit-lamp photographs for bleb morphology assessment.…”
Section: Discussionmentioning
confidence: 81%
“…With our protocol of management, we performed needle revision with 5-FU rather than administering additional glaucoma medications. In reviewing previous studies, bleb functionality may relate with not only vascularity but also bleb height, bleb wall thickness, etc 22,33. This may explain the insignificant correlation of IOP with vascularity densities (color and brightness densities, vascularity scores of IBAGS and MBGS).…”
Section: Discussionmentioning
confidence: 96%